Structure of GeO2 Glass under Compression Using Molecular Dynamics Simulation - Mai Anh, Nguyen; Thi Thu Trang, Nguyen; Thi Nguyet, To; Van Linh, Nguyen (VNU Journal of Science: Mathematics - Physics; Vol 37 No 1DO - 10.25073/2588-1124/vnumap.4445, 2021)
We have investigated the behavior of GeO2 at the temperature of 300 K and the pressure from 0 to 100GPa by using the molecular dynamics simulation (the model with 5499 atoms). The results show that the Ge-Ge, Ge-O bond distance increase but O-O bond distance decreases when increasing the pressure. We find that the peak splitting of Ge-Ge at high pressure corresponds with the Ge-O-Ge and O-Ge-O bond angles. We also find that O-Ge-O bond angle decreases, and Ge-O-Ge bond angle increases with pressure. The core-sharing-bond is major at ambient pressure, but fractions of edge and face-sharing-bonds increase with pressure.